The Influence of Digital Marketing, Physical Evidence, and Price on Customer Satisfaction in the Coffee Shop Industry - Iswanto; Sulasti; Ana Yuliana (Journal of Economic Education and Entrepreneurship Studies, 2024)
The competition in the business world has intensified, with companies in Indonesia striving to increase their market share and attract new consumers. This study aims to explore the impact of digital marketing, physical evidence, and pricing on customer satisfaction at CW Coffee Tanjung Sari in Pontianak City. The research employs a quantitative approach, focusing on individuals who have visited and purchased products from the CW Coffee Tanjung Sari branch. The study uses purposive sampling to select respondents, ensuring that the sample represents the target population effectively. Data were analyzed using descriptive statistics, validity and reliability tests, and multiple linear regression analysis, including the t-test. The findings reveal that digital marketing does not significantly influence customer satisfaction, while physical evidence and pricing have significant and positive effects on customer satisfaction. These results underscore the importance of tangible elements and competitive pricing in enhancing customer satisfaction, while also suggesting that digital marketing may need to be reevaluated or adjusted to better meet customer needs and expectations in this context.